PENERAPAN METODE THINK PAIR SHARE DALAM PEMBELAJARAN MENULIS PUISI PADA SISWA KELAS X SMA NEGERI 1 SURANENGGALA TAHUN PELAJARAN 2024/2025 - Palinah; Tobroni; Muhammad Sholeh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the effectiveness of the use of the think pair share method in poetry writing learning activities and to describe the learning activities carried out in class X students at SMA Negeri 1 Suranenggala. The research method applied is quasi-experimental with a nonequivalent control group design. Data analysis revealed a significant difference between the pretest and posttest scores of the two groups. The average pretest score of the experimental class was 61.5 and increased to 81.31 in the posttest, with a difference of 19.81 points. While in the control class, the average pretest score of 60.36 increased to 67.36, with an increase of only 7.00 points. The results of the t-test showed a t-count value of 14.823> t-table 2.074, which means that H1 is accepted and H0 is rejected. These findings indicate that the cooperative learning strategy is effective in increasing creativity, understanding of the material, and active participation of students. The implications of this research are expected to contribute to the development of Indonesian language learning models that are more innovative and responsive to student characteristics.